Motor skills, visual perception, and visual-motor integration in children and youth with Autism Spectrum Disorder. (August 2022) - Faber, Leila; van den Bos, Nellie; Houwen, Suzanne; Schoemaker, Marina M.; Rosenblum, Sara
Abstract: Background: Motor skill deficits are prevalent among children with Autism Spectrum Disorder (ASD) however, little is known about the underlying mechanism of these deficits. In response to this gap, this study investigated how visual perception (VP) and visual-motor integration (VMI) are associated with motor skills among children and youth with ASD. Methods: Sixty-seven individuals with ASD and sixty-seven age- and gender-matched individuals without ASD (age range: 9.83–15.13 years) participated. Motor skills were assessed with the Movement Assessment Battery for Children-2 (MABC-2) and VP and VMI with the respective components of the Beery-Buktenica Developmental Test of Visual-Motor Integration-6 (Beery VMI-6). Results: Significantly more children and youth with ASD were in the red and orange zone of the MABC-2 traffic-lighting system for the total MABC-2 and the Aiming and Catching and Balance components compared to the children and youth without ASD. Both groups did not differ on the VP and VMI components of the Beery VMI-6. Pearson correlations between VP and VMI, and motor skills were weak but significant for the individuals without ASD, but not for the ASD group. Conclusion: The current study added to the evidence about motor skill deficits among children and youth with ASD. VP and VMI were not related to motor skills, suggesting that these functions – as measured in the current study – are no underlying mechanisms of motor skill deficits of children with ASD and average intelligence. Diagnostic implications are provided for the evidence of motor skill deficits among children and youth with ASD. Highlights: Results suggests motor skill deficits among children and youth with Autism Spectrum Disorders (ASD). VP and VMI – as measured in the current study – were not related to motor skills among children and youth with ASD. VP and VMI – as measured in the current study - are no underlying mechanisms of motor skills deficits of children with ASD. Diagnostic implications are provided for the evidence of motor skill deficits among children and youth with ASD.